Theory of Nonlinear Implicit Fractional Differential Equations - Kucche, Kishor D.; Nieto, Juan J.; Venktesh, Venktesh (Differential equations and dynamical systems, 2020)
This paper deals with the basic theory of nonlinear implicit fractional differential equations involving Caputo fractional derivative. In particular, we investigate the existence and interval of existence of solutions, uniqueness, continuous dependence of solutions on initial conditions, estimates on solutions and continuous dependence on parameters and functions involved in the equations. Further, we study ε -approximate solution of the implicit fractional differential equations.